TAX MANAGEMENT STRATEGY: AN ACCOUNTING APPROACH IN A GLOBAL CONTEXT (SDG 8: DECENT WORK AND ECONOMIC GROWTH) - Sudiati, Rochma; Khairunnisa, Hera; Prihatni, Rida; Muhammad Zairin, Gentiga; Fahrizal, Rifki; Alisha Putri, Siti; Saw Tek Wei, Andrew (Yayasan Education and Social Center, 2025)
This program focuses on enhancing tax compliance and literacy among Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, specifically targeting Bulak Village in Indramayu. MSMEs play a crucial role in the country's economy, contributing 61% of the GDP and providing 97% of employment. However, a significant gap exists in tax knowledge and compliance, with only a small fraction of MSMEs possessing a Taxpayer Identification Number (NPWP). This community service project aims to address these gaps by offering training and mentorship to MSME actors on tax regulations, financial reporting, and compliance with Indonesian tax laws. The program follows a structured approach based on goal-setting theory, consisting of phases such as goal setting, planning, training, and evaluation. By improving the financial literacy and tax awareness of MSME owners, the project fosters a sustainable and compliant business environment. The results highlight the importance of continued collaboration between local authorities, financial institutions, and educational institutions to enhance MSME support, ensuring better compliance and encouraging the use of digital tax tools for long-term growth and sustainability.